2022
DOI: 10.1177/08258597221082393
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Perceptions of Palliative Care Among the Elderly: A Qualitative Study

Abstract: Objectives: With the rapidly aging population worldwide, the demand for palliative care is increasing. Palliative care publicity and education must be further developed globally, especially for the elderly. It is essential to perform targeted promotion by understanding the awareness and needs of palliative care of the elderly. This study aimed to investigate elderly people's awareness of palliative care and their own views on and needs for palliative care, which could provide a basis for the popularization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Ultimately, new sub‐themes were discovered, including the specificity of the ICU context and less attention paid to palliative care in the ICU. These emerging sub‐themes may be associated with the public's concept, China's policy on the functional positioning of ICUs, as well as the limited experience of ICUs in providing palliative care 39,40 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, new sub‐themes were discovered, including the specificity of the ICU context and less attention paid to palliative care in the ICU. These emerging sub‐themes may be associated with the public's concept, China's policy on the functional positioning of ICUs, as well as the limited experience of ICUs in providing palliative care 39,40 …”
Section: Discussionmentioning
confidence: 99%
“…These emerging sub-themes may be associated with the public's concept, China's policy on the functional positioning of ICUs, as well as the limited experience of ICUs in providing palliative care. 39,40 Previous studies from other countries were mostly based on clinical experiences in palliative care. 24,41,42 In contrast, palliative care is not widely integrated into ICUs in China.…”
Section: The Specificity Of the Icu Contextmentioning
confidence: 99%
“…During this stage, numerous needs emerge regarding the care and well-being of the cancer patient and their caregivers which are not always acknowledged or identified. Recognition and awareness of these needs can ensure early access and comprehensive treatment for cancer patients with palliative care needs, while also meeting the needs of their caregivers [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of death and dying, and the role of hospices and palliative care, have found understanding among the public is mixed, with women and older people more commonly aware of the role of hospices ( 1 ). Lack of understanding can result in hospice care and community support being difficult to navigate ( 2 ), with hospice care underutilized, leading to calls for increased education and engagement ( 3 , 4 ). Early conversations about death and dying are helpful in providing care and preparing for loss ( 5 ) but can be challenging conversations to have ( 2 , 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research on death and dying has been conducted through traditional methods such as interviews and surveys ( 3 ), but these rarely include ‘public deliberation, whereby people engage collectively with an issue, consider it from all sides, and struggle to understand it’ ( 11 ). Challenges in public engagement around death and dying include resistance and lack of interest in planning ahead, a view that one is living rather than dying (even when experiencing significant or complex illness) and understanding how to demonstrate the relevance of the subject matter, beyond those experiencing death, dying or grief ( 12 ).…”
Section: Introductionmentioning
confidence: 99%